2016
DOI: 10.1128/aem.00395-16
|View full text |Cite
|
Sign up to set email alerts
|

Insensitivity of Diverse and Temporally Variable Particle-Associated Microbial Communities to Bulk Seawater Environmental Parameters

Abstract: There is a growing recognition of the roles of marine microenvironments as reservoirs of biodiversity and as sites of enhanced biological activity and in facilitating biological interactions. Here, we examine the bacterial community inhabiting free-living and particle-associated seawater microenvironments at the Pivers Island Coastal Observatory (PICO). 16S rRNA gene libraries from monthly samples (July 2013 to August 2014) were used to identify microbes in seawater in four size fractions: >63 m (zooplankton a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 50 publications
10
56
1
Order By: Relevance
“…Although GJAM clusters are generally distributed across the phylogenetic tree, a majority (18/20) of Bacteriodetes are assigned to nearshore clusters (e.g. Clusters 1, 4 and 7), which is consistent with their predicted role in degrading complex organic matter and associations with algae and other particles (FernĂĄndez-Gomez et al, 2013;Yung et al, 2016) as well as observations in the Columbia River Estuary system (Fortunato et al, 2013). Although we focus on the influence of distance along the transect, some GJAM clusters revealed temperature-only associations; for example, three of the four OTUs in SAR406 were positively associated with temperature (Cluster 8; Supporting Information Fig.…”
Section: Otu Level Patterns Across Transectssupporting
confidence: 59%
See 1 more Smart Citation
“…Although GJAM clusters are generally distributed across the phylogenetic tree, a majority (18/20) of Bacteriodetes are assigned to nearshore clusters (e.g. Clusters 1, 4 and 7), which is consistent with their predicted role in degrading complex organic matter and associations with algae and other particles (FernĂĄndez-Gomez et al, 2013;Yung et al, 2016) as well as observations in the Columbia River Estuary system (Fortunato et al, 2013). Although we focus on the influence of distance along the transect, some GJAM clusters revealed temperature-only associations; for example, three of the four OTUs in SAR406 were positively associated with temperature (Cluster 8; Supporting Information Fig.…”
Section: Otu Level Patterns Across Transectssupporting
confidence: 59%
“…Genomic DNA was subsequently cleaned using the Zymo OneStep PCR inhibitor removal kit and DNA was quantified using a Nanodrop ND-100. 16S rRNA genes from each sample were sequenced, using a dual-index sequencing approach as described previously (Kozich et al, 2013;Yung et al, 2016). PCR reactions contained 10 ng of template DNA, 1.25 U Econo Taq (Lucigen) and a final concentration of 1× Taq buffer, 200 ÎŒM dNTPs, 2 mM MgCl 2 and 0.5 ÎŒM of each primer.…”
Section: Dna Extraction and Library Preparationmentioning
confidence: 99%
“…Microbial communities were characterized using a dual index amplicon library approach targeting the 16S rRNA gene V3-V4 region (Kozich et al, 2013;Yung et al, 2016). PCR reactions contained 20 ng of template gDNA and 0.4 U of Q5 DNA polymerase (NEB, Ipswich, MA, USA) as well as a final concentration of 200 ÎŒM dNTPs, 2 mM MgCl 2 and 0.5 ÎŒM of each primer.…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…In particularly, some broad key functional gene categories involved in DOM utilization (Poretsky et al, 2010;Rinta-Kanto et al, 2012) and specific functional gene groups linked to successive decomposition of phytoplankton blooms (Teeling et al, 2012) are significantly different, indicating the fundamental differences in survival strategies in relation to potentially available substrates. It is further revealed that PA microbes generally have larger genomes with a variety of metabolic and regulatory capabilities of utilizing compositionally varied organic matter, while the genomes of FL microbes usually are smaller with streamlined metabolic and regulatory functions that enable efficient adaption to oligotrophic conditions (Smith et al, 2013;Yawata et al, 2014;Yung et al, 2016). Phylogenetically, PA and FL lineages generally exhibit different compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, most members of the PA and FL clades are generalists which switch their lifestyles via attachment and detachment to particles (Crespo et al, 2013;Li et al, 2015). As revealed in many marine niches, α-Proteobacteria, Îł-Proteobacteria and Bacteriodetes are the major overlapped phyla in both PA and FL microbial fractions (Yung et al, 2016).…”
Section: Introductionmentioning
confidence: 99%